Accountability in Islamic financial institution: The role of the Shari'ah supervisory board reports. Issue 1 (7th January 2019) - Aribi, Zakaria Ali; Arun, Thankom; Gao, Simon
Abstract : Purpose: The purpose of this paper is to explore whether any discrepancy exists between the disclosed in SSB reports of Islamic banks and the disclosure index which was based on stakeholders' expectation. Design/methodology/approach: This study uses contents analysis as the research method to explore Shariâ'ah audit reporting practices of Islamic Banks. Findings: The study finds that the level of disclosures overall by IFIs in the sample is rather low compared to the stakeholder expectations. Practical implications: This paper has important implication for policy makers as it contribute to the debate on that uniform disclosure standards across the globe need to be implemented to ensure a uniform level of disclosure by Islamic banks. Originality/value: This study is amongst the few studies that examine and explore the nature and extent of Shari'ah Supervisory Board in Islamic banks.